Research on Corrosion Damage and Bearing Characteristics of Bridge Pile Foundation Concrete under a Dry-Wet-Freeze-Thaw Cycle - Zhongju Feng; Jianwei Huo; Haibo Hu; Ruixin Zhao; Fuchun Wang; Guan Jiang; Xianhua Yao; Tie Li; Zhenyu Song (Advances in Civil Engineering)
This study investigated the corrosion damage and bearing characteristics of bridge pile foundations under a dry-wet-freeze-thaw cycle of composite salt in an alpine salt marsh area using an in situ test, laboratory test, and numerical simulations. The in situ test showed that the dry-wet-freeze-thaw cycle has little effect on the quality of the concrete specimens and rebar. The area of the rebar at a depth of 0.25 m had the highest corrosion rate of 91%. The application of epoxy resin on the surface improved erosion resistance. After one year of outdoor dry-wet-freeze-thaw cycle test, due to the interaction of compound salts, the quality of specimens is reduced under the denudation of chloride ions, while the mass of specimens is increased by the corrosion products formed under the joint action of carbonate and sulfate, resulting in less obvious change of specimen quality, the antierosion coefficient of the specimens decreased, the maximum loss rate of compressive strength was 38.2%, and the pile foundation began to deteriorate. The laboratory test showed that expansive substances, such as Friedel salt, appeared in the concrete specimens of pile foundation during 225 cycles of dry-wet-freeze-thaw cycles, the relative dynamic elastic modulus was reduced by 60.9%, the antierosion coefficient was reduced to 0.51, and the compressive strength loss rate was 65.9%. As such, the pile foundation was seriously damaged. The numerical simulation shows that, with an increase of the peeling thickness and the corrosion depth, the bearing capacity of the pile foundation will gradually decrease after 8 years. Without maintenance, the bearing capacity of a pile foundation will decrease by 34.45% in the 20th year.